Imagens discursivas de imigrantes e suas implicações no discurso de receptividade do brasileiro na imprensa nacional: uma perspectiva dialógica - Dugnani, Bruna Lopes Fernandes (2017)
This doctoral dissertation is based on the hypothesis that the forms for reporting speeches of and about immigrants used by the Brazilian press and the relationship between what is stated in these reported speeches and the discourses that have been part of Brazil’s historicization show that the discourse of Brazilian receptivity has been produced by a dialogic tension among the different values attributed to immigrants. Therefore, we aim to comprehend how the images of contemporary immigrants can be perceived in the Brazilian press and how they impact the Brazilian self-description as a receptive people. We adopted the following criteria for the corpus selection, comprised of journalistic texts: they were about contemporary immigration in Brazil; they were published in 2012 by Folha de S. Paulo, O Globo, Época, and Veja; they allowed the identification of discursive images of immigrants; and they presented different forms to represent foreigners. We established those criteria due to the hypothesis put forward in this dissertation, the media companies’ reach and great influence in forming public opinion, and the coincidence there was between the publication date of those texts and the outset of the preparation of a new national policy on immigration by a team of staff members of SAE [Bureau for Strategic Issues of the President of the Republic]. This way we collected 9 journalistic texts. In order to achieve the objective of this research, we draw on the Bakhtinian theoretical and methodological perspective and, more specifically, on the concepts of identity and alterity. We also discussed national identity, otherness in immigration, peculiarities of the journalistic sphere and the news report genre, the concept of object memory and forms of reported speech. For the purpose of guiding the development of this study, we addressed the following questions: 1) How does immigration memory in the press take part in Brazil’s historicization? How does the contemporary press modify this memory by employing different forms to report speeches of and about immigrants? and, 3) What is the impact of this memory and its modification on the discourse of Brazilian receptivity? As a result, we noticed that the journalistic texts published between the years of 1808 and 1939 (period that includes the Brazilian press establishment and the major migratory flows to Brazil) enunciated discourses related to civilization, anti-Portugueseness, nationalism, assimilationism, miscegenation, and racial whitening. Such discourses produced different discursive images of immigrants, which contributed to deconstruct and resonate the national myth of Brazilian receptivity as they praised their receptivity, omitted the violence and prejudice towards foreigners, singularized the negative events and drew on common sense regarding what was considered undesirable by anyone at the time. We also observed that the different forms used by the Brazilian contemporary press to report the discourses about and of contemporary immigrants fostered different ways to integrate the reported speech into the journalistic texts, thus implicating images of immigrants not only as adapted, non-adapted, (un)desirable people, but also as overload social budgets, lawbreakers and commodities. On the one hand, these discursive images echoed the conceptions of the ideal immigrant as someone who is in accordance and integrated to the Brazilian society, a worker and a person who brings benefits to the Brazilian society and economy. On the other hand, they also produced adjustments to the past discourses as they resignified the concept of “adapted,” changing it to globalized, broadening the understanding of what a good worker is in order to include new positions that are needed in the country and recontextualizing the discourses about the expenses that the immigrants can represent by taking into consideration the new Brazilian social assistance programs. These discourse echoes and actualizations showed the dialogic tensions that are inherent to the discourse of Brazilian receptivity. We believe that this study might contribute to demystify the discourse that Brazilian people are receptive and to understand the images attributed to immigrants in Brazil. Thus, it might provide a better understanding of an issue that has been standing out and influencing the outset of new laws and national policies and the social and international affairs involving Brazil